2022
DOI: 10.1186/s12891-022-05906-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficacy of a single intraarticular injection of platelet-rich plasma (PRP) combined with different hyaluronans for knee osteoarthritis: a randomized-controlled clinical trial

Abstract: Background Intraarticular plasma-rich platelet (PRP) and hyaluronic acid (HA) have each been shown to be effective for treating knee osteoarthritis (OA). Evidence supporting the combination therapy is controversial. This study aimed to investigate the efficacy of a single intraarticular PRP injection combined with different HAs in patients with knee OA. Methods In this prospective randomized-controlled trial, 99 patients with Kellgren-Lawrence grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…On the contrary, the HA group witnessed a decline of 21 points, or approximately 61%, as opposed to the initial count of 55. According to established criteria, a pain reduction of at least 30% is indicative of significant clinically relevant changes, which means that the study had a positive outcome [28,29]. The present data suggest that m-PRP is superior to the m-HA preparation used in this study.…”
Section: Discussionmentioning
confidence: 50%
“…On the contrary, the HA group witnessed a decline of 21 points, or approximately 61%, as opposed to the initial count of 55. According to established criteria, a pain reduction of at least 30% is indicative of significant clinically relevant changes, which means that the study had a positive outcome [28,29]. The present data suggest that m-PRP is superior to the m-HA preparation used in this study.…”
Section: Discussionmentioning
confidence: 50%
“…The higher the score, the more severe the condition and the worse the functional condition. 17 Simultaneously, Western Ontario and McMaster Universities Osteoarthritis Index Score (WOMAC) was used to evaluate patients’ bone and joint pain, stiffness, and physical dysfunction. This scale contains 24 questions and is divided into three subcategories: pain (five items), stiffness (two items), and physical dysfunction (17 items).…”
Section: Methodsmentioning
confidence: 99%
“…Various nonoperative treatments for knee osteoarthritis were evaluated in the last year. An RCT comparing the efficacy of a single intra-articular injection of platelet-rich plasma combined with 2 different hyaluronans (platelet-rich plasma and hyaluronan #1 compared with platelet-rich plasma and hyaluronan #2) for the treatment of Kellgren-Lawrence grade-2 knee osteoarthritis showed significant improvements in pain reduction (change in visual analog scale [VAS] pain score from baseline to 6 months after the injections) for both groups 4 , whereas a systematic review and meta-analysis evaluating the efficacy of intra-articular platelet-rich plasma combined with mesenchymal stem cells also revealed that such a combination significantly reduces knee pain 5 . However, none of these studies included a placebo control group.…”
Section: Osteoarthritis Of the Kneementioning
confidence: 99%